Increased New lncRNA–mRNA Gene Pair Levels in Human Cumulus Cells Correlate With Oocyte Maturation and Embryo Development. (August 2015) - Li, Juan; Cao, Yunxia; Xu, Xiaofeng; Xiang, Huifen; Zhang, Zhiguo; Chen, Beili; Hao, Yan; Wei, Zhaolian; Zhou, Ping; Chen, Dawei
The close relationship between cumulus cells and oocyte indicates that the analysis of cumulus gene expression is a potential noninvasive method to aid embryo selection and in vitro fertilization outcome. Long noncoding RNAs (LncRNAs) could regulate essential pathways that contribute to human oocyte maturation, fertilization, and embryo development, which indicates that lncRNA would be valuable biomarkers. In our previous study, AK124742 is a newly detected lncRNA that was identified as being natural antisense to PSMD6, but its role in oocyte and embryo development is still not elucidated and needs to be investigated. Here, the expression of AK124742 and PSMD6 was measured in 40 pairs of cumulus cells from oocytes that result in high-quality embryos (HCCs) and from oocytes that result in poor-quality embryos (PCCs) by real-time quantitative reverse transcriptase polymerase chain reaction. The predictive value of AK124742 and PSMD6 was evaluated using a receiver–operating characteristic (ROC) curve. Notably, elevated expression levels of AK124742 and PSMD6 were observed in HCCs compared to PCCs (72.5% and 62.5%, respectively; P < .01). Expression of AK124742 was potentially positively associated with the PSMD6 levels. The relative expression levels of AK124742 and PSMD6 in the pregnancy group were significantly higher than those in the nonpregnancy group ( P < .01).The area under the ROC curve of AK124742 was 0.78 (95% confidence interval: 0.64-0.93). In conclusion, AK124742 and PSMD6 as a new lncRNA–messenger RNA gene pair in human cumulus cells may be considered as potential biomarkers to aid embryo selection.